Synthesis of monetary theories - Sahara, Takaomi (Rutland, Vt. : Japan Publications Trading Co., 1964)
The book is divided into three parts: The Concept of Money, The Circulation of Money and The Value and Quantity of Money.
Includes index
rpm 25/01/2019
Loans
Keywords: Money